STUDI TENTANG BRAND LOYALTY KENDARAAN NIAGA DI SEMARANG - Sutanza, Bangkit; Widiyanto, Ibnu (Diponegoro Journal of Management, 2013)
Brand loyalty is one of the important components in the automotive industries. Optimal management of brand loyalty that needs to be done, because brand loyalty of brand loyalty can be influencing sales and determine profitability in the future. The purpose of this study was to investigate the influence brand reputation, brand predictability, brand competences and brand liking to brand loyalty. After doing a literature review and hypothesis formulation, data is obtained by spreading questionnaires to 100 owner and user of Mitsubishi commercial vehicles in Semarang. Using purposive sampling, and then data is analyzed quantitatively and qualitatively. Quantitative analysis covers some matters; they are validity and reliability test, classic assumption text, analysis multiple regression, and hypothesis test. The hypothesis test is done through t and F test, and coefficient of determination (R2). The result of this study shows that coefficient of determination in Adjusted R Square is 0.899, which means that 89,9% brand loyalty effect can be explained by four independent variables in this study that are brand reputation, brand predictability, brand competence and brand liking, and the rest 10,1% can be explained by other variables outside the model of this study.